Effects of Aphloia theiformis on key enzymes related to diabetes mellitus - Marie Carene Nancy Picot; Mohamad Fawzi Mahomoodally (Taylor & Francis Group, 2017)
Context: Aphloia theiformis (Vahl.) Benn. (Flacourtiaceae) (AT) is traditionally used for the management of diabetes mellitus (DM), but there is no scientific data regarding activity against enzymes linked to this condition. Objective: To evaluate the kinetics of AT on key enzymes inhibition related to DM, and establish the antioxidant profile of AT. Materials and methods: Dried powdered AT leaves were used to prepare crude methanol extract (70% v/v) (CME). Kinetics of CME (5000 to 156.25 μg/mL) on α-amylase, α-glucosidase, and lipase inhibition were studied. CME was partitioned using solvents of increasing polarity and kinetics of enzyme inhibition of each fraction (1000-31.25 μg/mL) was evaluated. Potent fractions were combined to assess any synergistic effect. Total phenol, flavonoid, tannin, anthocyanin contents, and antioxidant capacity of AT was evaluated using standard spectrophotometric methods. Results: CME, ethyl acetate, and n-butanol fractions showed potent inhibitory activities against the enzymes with IC50 ranging from 22.94-939.97 μg/mL. Significant (p < 0.05) reduction in IC50 (15.72 and 157.03 μg/mL against α-amylase and lipase, respectively) was observed when ethyl acetate and n-butanol fractions were combined; showing synergism. The extracts showed noncompetitive inhibition against α-amylase and α-glucosidase. Ethyl acetate, n-butanol fractions, and CME showed highest antioxidant capacities (0.44-1.41 μg GAE/mg sample), and phenol content (211.74-675.53 μg GAE/mg sample). Conclusion: This study supports the use of AT in the management of DM and provides the rationale for bioactivity guided isolation and characterization of compounds from the ethyl acetate and n-butanol fractions.